Cytogenetic analysis in the incertae sedis species Astyanax altiparanae Garutti and Britzki, 2000 and Hyphessobrycon eques Steindachner, 1882 (Characiformes, Characidae) from the upper Paraná river basin - Martinez, Emanuel R. M. [UNESP]; Alves, Anderson L. [UNESP]; Silveira, Sara M. [UNESP]; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP] (Pensoft Publishers, 2012)
Cytogenetic analyses were accomplished in two populations of Astyanax altiparanae Garutti & Britzki, 2000 and one population of Hyphessobrycon eques Steindachner, 1882, considered incertae sedis in Characidae family. Two populations of A. altiparanae (Mogi-Guaçu and Tietê rivers) presented 2n=50, with the same karyotype formula: 6M+12SM+20ST+12A (FN=88). H. eques from Capivara river presented 2n=52 and karyotype formula 14M+16SM+4ST+18A (FN=86). In each karyotype, the nucleolus organizer regions were detected at the end of the short arm of a single medium-sized subtelocentric chromosome. The Chromomycin A3 (CMA3) marking is coincident for the NORs in chromosomes of the two species and present additionally in two different chromosomes of A. altiparanae thus showing interpopulation differences in this species. In H. eques, weak heterochromatic blocks in the position of centromeres and telomeres of most chromosomes and negative C-banding for the NOR bearing chromosome were visualized. The obtained results contribute both to the understanding of karyotype evolution of these species and to the clarifying their phylogenetic relationships. © E.R.M. Martinez et al.
Keywords: Ag-NOR; Chromosomes; Evolution; Neotropical fish